PERSEPSI STAKEHOLDER TERHADAP PENGEMBANGAN BADAN USAHA MILIK DESA (BUMDES) DI SUNGAI LANGKA, KECAMATAN GEDONG TATAAN KABUPATEN PESAWARAN - Tri Pujiana; Dwi Arianti; Abdul Mutolib (Universitas Galuh Ciamis, 2019)
This study aims to analyze stakeholder perceptions of the development of the Ramaksa Village-Owned Enterprises (Bumdes) on the Sungai Langka. This research is descriptive with data collection done qualitatively using in-depth interview guidelines then analyzed content (content analysis). The study was conducted at the Bumdes Ramaksa in Sungai Langka Village, Gedong Tataan Subdistrict, Pesawaran District. The technique of determining informants used purposive sampling technique. The research subjects were stakeholders, namely the Head of the Sungai Langka, operational implementers and two people from Sungai Langka. The research was conducted in November 2018. The focus of this research was the existence of Bumdes, the contribution of the Bumdes in strengthening the economy and village development as well as stakeholder perceptions of the development of the Bumdes Ramaksa in the Sungai Langka. The results showed that the business units run by the Bumdes Ramaksa included drinking water refill management business units, microfinance institutions, livestock, and Izaura drinking water sub-agents. The selection of this business unit is based on the resources and potential in the Sungai Langka. The business entity owned by the village of Ramaksa was formed based on the principle of benefits and improving the welfare of the village community. Stakeholder perceptions of the development of the Bumdes Ramaksa are viewed from four aspects, namely economic, ecological, social and institutional aspects. Of the four aspects assessed, the Bumdes Ramaksa has been classified as good. According to the informant, the Bumdes program as an implementation of the community empowerment program seeks to create growth in the field of people's economy and equitable welfare through the expansion of business opportunities for small-scale business people as measured by increased income.